2006
DOI: 10.1248/jhs.52.252
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Stress Effect of BRAND'S Essence of Chicken (BEC) on Plasma Glucose Levels in Mice Loaded with Restraint Stress

Abstract: We investigated the effect of BRAND'S Essence of Chicken (BEC) on the basic metabolism of blood glucose in mice loaded with restraint stress. In the glucose intravenously treated mice, the stress prolonged the half-life period (T 1/2 ) of elimination for blood glucose from 51.7 to 62.2 min. The elimination rate decreased to 82.5% per min in stressed mice compared with a starved control. The T 1/2 of blood glucose was 55.2 min in the BEC treated group. BEC alleviated a stress-induced decrease in blood glucose. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 20 publications
0
19
1
Order By: Relevance
“…In research, different types of stress have been applied on animals to study their influences on glucose metabolisms, including endoplasmic reticulum stress, oxidative stress, restraint stress, and so on (34 -36). The present study employed a 20-h restraint stress to study its effects on glucose metabolism in mice (26). Results showed that restraint stress lead to glucose metabolism disorder in mice, which was reflected by abnormal glucose tolerance level, lowered glucose elimination rate, and decreased hepatic and muscle glycogen contents.…”
Section: Discussionmentioning
confidence: 87%
“…In research, different types of stress have been applied on animals to study their influences on glucose metabolisms, including endoplasmic reticulum stress, oxidative stress, restraint stress, and so on (34 -36). The present study employed a 20-h restraint stress to study its effects on glucose metabolism in mice (26). Results showed that restraint stress lead to glucose metabolism disorder in mice, which was reflected by abnormal glucose tolerance level, lowered glucose elimination rate, and decreased hepatic and muscle glycogen contents.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, Ricart-Jané's study (3) indicated that stress caused lipid energy-substrate redistribution between tissues, which was required for the fight-or-flight response. Other studies also indicated that stress limited the supply of energy, which lead to poor utilization of biological energy sources, neurological or tissue dysfunctions, and resulted in tiredness and various other physiological disorders (4,5). Stress is also well known for its direct influences on the central nervous system (6).…”
Section: Introductionmentioning
confidence: 99%
“…Human study demonstrated such effects as improvement of nasal mucus secretion, 3) sustaining strength in strenuous, repetitive exercise, 4) enhancement of the metabolic rate, 5,6) improvement of the serum iron level recovery after blood donation, 7) increases in beneficial contents in maternal milk, 8) and improvement of skin conditions. 9) Furthermore, in animal studies, inhibition of blood pressure increase 10,11) and attenuation of stress-induced response such as a decrease in blood glucose and lipid metabolism 12,13) have been reported. Thus, scientific evidence on the healthful effects of chicken soup or extract is gradually accumulating.…”
Section: Introductionmentioning
confidence: 99%